The Influence of Family Dynamics on the Mental Health of Women in Rural Pakistan: A Sociocultural Perspective - Musarrat Parveen; Saleha Qamer; Adeeba Inam; Bushra Nagaria; Syeda Marium Raza; Muhammad Asif, (Dialogue Social Science Review (DSSR), 2025)
This research investigates the manner which family relationships affect women's mental health in Pakistan rural areas by studying domestic violence alongside cultural rituals and financial matters. Research data were collected from forty women between 18 to 45 who reside in Pakistan's rural regions. Domestic violence affected 72.5% of participants while physical abuse together with emotional abuse and economic abuse remained widespread. Research results indicate that anxiety affected 65% of participants and depression affected 55% of the sample. Bride exchange practices known as watta satta triggered psychological distress because sixty percent of women experienced feeling stuck in their marital relationships. Seventy percent of study participants developed mental health issues because of financial instability and poverty. The high mental health burden was met with limited professional help reaching 25% of the population because cultural stigma and scant service availability existed. Research findings show the necessity of developing mental health and socioeconomic treatment protocols which preserve local cultural traditions in order to enhance support access for Pakistan's rural female population.